Analysis Cash On Delivery Cost Efficiency on Shopee Sharia Based Ethical Perspective User Satisfaction - Juang, Muhammad Juang Harfian; Euis Amalia; Roikhan Mochamad Aziz (Al-Mashrof: Islamic Banking and Finance, 2025)
This study examines the efficiency of Cash On Delivery (COD) handling costs and their impact on user satisfaction within Indonesia’s digital marketplace, framed within the context of Islamic fintech and sharia-based financial ethics. In Islamic financial systems, payment mechanisms are required to uphold the principles of justice, transparency, mutual consent, and social welfare. Using a quantitative approach, data were collected from 210 Shopee users and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal a significant negative relationship between COD handling costs and user satisfaction, indicating that higher and less transparent costs reduce perceived value and consumer trust. These results highlight that cost efficiency grounded in sharia ethical principles is essential for strengthening consumer protection and sustaining the credibility of Islamic fintech ecosystems.   Keywords: Cash On Delivery Efficiency, Handling Cost Analysis, User Satisfaction, Consumer Trust, Ethical Business Values